Asset Seizure as an Effort to Recover State Assets Resulting from Criminal Corruption - Nugroho, Hibnu; Budiyono, Budiyono; Ramadhani, Setiawan; Rantau, Palupi; Barkhuizen, Jaco (Faculty of Law, Universitas Negeri Semarang, 2026)
This research analyzes the effectiveness of asset forfeiture for corruption crimes in the Purwokerto District Prosecutor’s Office jurisdiction and designs future legal mechanism reconstruction using empirical juridical Research and Development (R&D) approach. Background reveals Indonesia’s Corruption Perceptions Index (CPI) stagnation at score 37 (rank 99/180 countries) in 2024, state losses Rp45.7 trillion versus <6% asset recovery, stalled Asset Forfeiture Bill in 2025 Prolegnas, and systemic in personam failure (KUHAP Article 39). Findings show Purwokerto effectiveness <50% due to systematic asset diversion patterns to family/third parties, post-verdict temporal gaps, weak Kejari-BPN-bank-PPATK coordination, forensic asset HR deficits, and LHKPN digital technology gaps. Emblematic cases Hendy Boedoro, Surya Darmadi, plus local PNPM Kedungbanteng-CV Jasa Pembangunan illustrate structural weaknesses. Reconstruction proposes Non-Conviction Based Asset Forfeiture (NCB) praconviction, dual track model PNS (Conviction Based via LHKPN) vs private sector (60-day reverse burden of proof), integrated IT platform AI forensic-blockchain land certificates, 20 prosecutors/kejari Asset Task Force, 24-hour inter-agency SLA, UNCAC harmonization 50 bilateral MoUs, and three-pillar political law with real-time transparent dashboard. 70% recovery target within 36 months realizes Peter Alldridge’s “crimes does not pay” doctrine, transforming Indonesia’s corruption law enforcement to global standards.